Organic profiles of brake wear particles - Alves, Célia (2021)
Four brake pads were tested in a bench dynamometer under test cycles with different braking severities: i) two types of conventional brake pads (low steel 1 and 2), and ii) two types of non-asbestos organic brake pads (NAO 1 and 2) with non-ferrous materials. Wear particles (PM10) were analysed for total carbon by a thermo-optical method and then solvent-extracted and analysed by gas chromatography–mass spectrometry. In general, the test protocols with less braking and lower temperatures gave rise to much lower PM10 levels. Total carbon accounted for PM10 mass fractions in a wide range (5.07–75.4%), generally decreasing with the severity of the braking cycles. More than 150 organic compounds were quantified, comprising aliphatics, polycyclic aromatic hydrocarbons (PAHs), alcohols, several types of acids (alkanoic, alkenoic, diacids and others), glycol/glycerol derivatives, plasticisers, sugars, sterols and various phenolic constituents. Globally, larger amounts of most of these compounds were emitted by NAO 2 under the smoothest braking cycle. Several correlations between compounds with the same functional groups were established. No PAH with five or more benzenic rings was detected. The differences in composition and concentrations are discussed based not only on the characteristics of the braking circuits, but also on the diverse quantities and types of organic compounds used in the brake pad formulations.